INTEGRATED ELECTRICAL CONTROL PANELS USING JAVA PROGRAMING - Suprapto Suprapto (Jurnal Penelitian Saintek, 2005)
Technology trend nowadays is  connecting  one  instrument with  itothers  to  be  an  integrated system  that  can  ease  human's  work.Integrated Control Panel is  an  electricity control panel  which is controlled remotely. This control panel  is  so  much because of its efficiency which is gained and more than one instrument which are controlled. This control panel is  a remote controlled that can ease human's work, do security control and self control. This research a  . started from  software and hardware plan making and implementing the result of the analytic technique is  used to answer whether theresearch on remote sensing using Web can be more efficient and makehuman's work easier. The result of the analytic technique is shown bythe speed of access time between the client and  the server. From thefinding it can be conclude that Integrated Control Panel which can be controlled through web browser can be ease human's work in doingcontrol  access  to  electricity  instruments.  This  control  method  isobviously more efficient because of small access time. This is shown by the mean of access time which is only 265 milliseconds. This panelis provide with database system to save data control. This databasecan be accessed to know the data control.